Supervisors and Performance Management Systems - Anders Frederiksen; Lisa B. Kahn; Fabian Lange (Institute of Labor Economics (IZA), 2017)
Supervisors occupy central roles in production and performance monitoring. We study how heterogeneity in performance evaluations across supervisors affects employee and supervisor careers and firm outcomes using data on the performance system of a Scandinavian service sector firm. We show that supervisors vary widely in how they rate subordinates of similar quality. To understand the nature of this heterogeneity, we propose a principal-agent model according to which supervisors can differ in their ability to elicit output from subordinates or in their taste for leniency when rating subordinates. The model also allows for variation in how informed firms are about this heterogeneity. Within the context of this model, we can discern the nature of the heterogeneity across supervisors and how informed firms are about this heterogeneity by relating observed supervisor heterogeneity in ratings to worker, supervisor, and firm outcomes. We find that subordinates are paid significantly more, and their pay is more closely aligned with performance, when they are matched to a highrating supervisor. We also find that higher raters themselves are paid more and that the teams managed by higher raters perform better on objective performance measures. This evidence suggests that supervisor heterogeneity stems, at least in part, from real differences in managerial ability and that firms are at least partially informed about these differences. We conclude by quantifying how important heterogeneity in supervisor type is for workers' careers. For a typical worker, matching to a high rater (90th percentile) relative to a low rater (10th percentile) for just one year results in an increase in the present discounted value of earnings equivalent to 7 14% of an annual salary.
Keywords: M5; 330; labor; personnel economics; principal-agent; performance management systems; supervisors; organizational economics